KOMUNIKASI PERSUASIF PENYULUH AGAMA HINDU DI BANJAR CEMENGGON DESA PENARUNGAN KECAMATAN MENGWI KABUPATEN BADUNG - Purnama Dewi, Ni Made Mira; Wirta, I Wayan; Laksana Utama, Putu Kussa (Institut Hindu Dharma Denpasar, 2019)
The importance of growing people?s interest the teachings conveyed by instructors to the Banjar Cemenggon community is a big challenge for PNS Hindu Religious Extension. The presence of Hindu Religious Extension is expected to be able to answer all phenomena that occur in the Banjar Cemenggon community. Based on the background above, the problem is: 1) What is the existence of the Hindu Religious Extension in Banjar Cemenggon, 2) What is the strategy of Persuasive Communication of Hindu Religion in Banjar Cemenggon? 3 What is the impact of the Persuasive Communication of Religious Extension in Banjar Cemenggon?The theories used in the research are: 1) Structural Functional Theory, 2) Persuasive Communication Theory, 3) Communication Effect Theory. This study uses qualitative research techniques. The technique of presenting the results of the study is by descriptive technique. This study found 1) The existence of extension agents in Banjar Cemenggon is characterized by providing programs targeting certain groups, namely: BKB (toddler family guidance), BKR (adolescent family guidance), BKL (guidance for elderly families). 2) Persuasive Communication Strategy that is used in three stages, namely the initial stage, namely the approach to the teacher, the implementation phase is characterized by counseling dharma discourse and technical guidance, and the final stage is by evaluation. 3) The impact that occurred on the Banjar Cemenggon community, namely: cognitive impact when the community understood the message conveyed by the instructor, the affective impact was marked by the community's interest in counseling, and the impact of behavior when the community was able to make upakara facilities in accordance with the counselor's appeal.